TUBERCULOSIS PADA ANAK - Irwandi, Irwandi; Fetria Faisal; Hiddayaturrahmi, Hiddayaturrahmi (Nusantara Hasana Journal, 2025)
Tuberculosis (TB) in children remains a significant global health problem, particularly in countries with high transmission rates. Children are more susceptible to rapid progression into severe forms of TB, such as TB meningitis and miliary TB, due to their immature immune systems. Diagnosing TB in children is challenging because symptoms are often nonspecific and bacterial loads are low, leading to frequent negative bacteriological results. Common clinical manifestations include persistent cough, prolonged fever, weight loss, and failure to thrive. Major risk factors include close contact with adult TB cases, malnutrition, and immunocompromised conditions. Diagnostic approaches require a combination of clinical evaluation, radiological examination, and immunological tests such as the tuberculin skin test or IGRA. Treatment follows standard antituberculosis drug regimens according to national guidelines. Preventive measures, including BCG vaccination and routine screening of household contacts, play a crucial role in reducing the incidence and complications of TB in children. Overall, early detection and comprehensive management are essential to decrease morbidity and mortality associated with pediatric TB.